The Aryl Hydrocarbon Receptor in Chronic Kidney Disease: Friend or Foe? - Mo, Yenan; Lu, Zhaoyu; Wang, Lixin; Ji, Chunlan; Zou, Chuan; Liu, Xusheng (Frontiers in Cell and Developmental Biology, 2020)
The aryl hydrocarbon receptor (AhR) is a ligand-activated transcription factor that promotes cell responses to small molecules derived from the diet, microorganisms, metabolism and pollutants. The AhR signal regulates many basic cellular processes, including cell cycle progression, adhesion, migration, apoptosis and cell proliferation. Many studies have shown that AhR is associated with chronic kidney disease (CKD) and its complications. This article reviews the current knowledge about the role of AhR in CKD, showing that AhR mediates CKD complications, including cardiovascular disease, anaemia, bone disorders, cognitive dysfunction and malnutrition, and that it influences drug metabolism in individuals with CKD. AhR enhances the intestinal barrier function to reduce the harmful effects of uremic toxins. Therefore, understanding the complex roles of AhR during CKD is important to be able to target this transcription factor safely and effectively for CKD prevention and treatment.